Penerapan Terapi Dzikir Terhadap Efektivitas Penurunan Tekanan Darah Pada Pasien Stroke Hemoragic di ICU - Danang Tulus Prasetya; Hermawati Hermawati; Waluyo Waluyo (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension is the main trigger factor for stroke events, both hemorrhagic and ischemic strokes. One of the complications of hypertension is that it can cause an increase in peripheral blood pressure, causing a poor hemodynamic system and thickening of the blood vessels and hypertrophy of the heart muscle. Hypertension which continuously causes atherosclerotic plaque will trigger a stroke. Objective : to determine the results of applying dhikr therapy to reduce blood pressure in Hemorrhagic Stroke patients in the ICU. Method : Descriptive research using case studies, this application carried out blood pressure measurements before and after being given dhikr therapy, dhikr therapy was carried out 3 times a day for 3 days. Results : Blood pressure Mr. Y from 155/96 mmHg to 150/90 mmHg. Meanwhile, Mr. R from 156/116 mmHg to 148/94 mmHg. Conclusion : there was a decrease in blood pressure in both respondents after dhikr therapy.